2001
DOI: 10.1074/jbc.m105183200
|View full text |Cite
|
Sign up to set email alerts
|

Fast Coordination Changes in Cytochrome c Do Not Necessarily Imply Folding

Abstract: Folding of globular proteins occurs with rates that range from microseconds to minutes; consequently, it has been necessary to develop new strategies to follow the faster processes that exceed stopped-flow capabilities. Rapid photochemical methods have been employed to study the rate of folding of reduced cytochrome c. In this protein, the iron of the covalently bound heme binds a His and a Met, proximal and distal. Unfolding by guanidine or urea weakens the Fe-Met bond, and the reduced unfolded cytochrome c e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
3
32
1
Order By: Relevance
“…weakened by mutagenesis of the ligands. 36,37 It has been suggested that changes in co-ordination to the heme iron are not related to any folding events in cytochrome c. 38 In this current example of cytochrome b 562 , the changes in the protein fold and mobility that result in this weakening or loss of heme iron ligands appear to be limited mainly to the terminal stretches of sequence around these ligands, residues 1-15 and 88-106 (coloured yellow in state A in Figure 9). The folding of the ferrous holo protein 16,17 was initiated by reduction of the ferric protein in this compact state.…”
Section: Equilibrium Denaturation Of Holocytochrome B 562 Monitored Bmentioning
confidence: 91%
See 1 more Smart Citation
“…weakened by mutagenesis of the ligands. 36,37 It has been suggested that changes in co-ordination to the heme iron are not related to any folding events in cytochrome c. 38 In this current example of cytochrome b 562 , the changes in the protein fold and mobility that result in this weakening or loss of heme iron ligands appear to be limited mainly to the terminal stretches of sequence around these ligands, residues 1-15 and 88-106 (coloured yellow in state A in Figure 9). The folding of the ferrous holo protein 16,17 was initiated by reduction of the ferric protein in this compact state.…”
Section: Equilibrium Denaturation Of Holocytochrome B 562 Monitored Bmentioning
confidence: 91%
“…9 Notably, residues 3-15 and 88-100 (in the sequences around the ligand residues, 7 and 102 at either terminus of the protein) no longer gave daN(i,iC3) NOEs indicative of a-helical conformation. Additionally, there is a gap (residues [33][34][35][36][37][38] in the helical pattern corresponding to helix 2 of the native protein. Helix 3 (residues 62-82) of the native protein appeared completely intact in this species.…”
Section: Equilibrium Denaturation Of Holocytochrome B 562 Monitored Bmentioning
confidence: 99%
“…Furthermore, no peaks were detected at the position of the β or α band (523 nm or 550 nm, respectively). Heme ligands have previously been shown to influence the spectral behaviour in the 550-nm range (Arcovito et al 2001;Lee et al 2001). Upon addition of 300 mM imidazole to MP301, the dithionite-reduced spectrum resembled that of the other heme His 6 -tagged fusion proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different amounts (30 -90 M) of a NO solution were added anaerobically to produce the reduced NO-bound derivative. The instrument used for photolysis experiments has been described elsewhere (17) and uses a Nd-YAG solid-state laser with a 5-ns pulse (Quanta System HIL 101, second harmonic ϭ 532 nm, E ϭ 80 mJ/pulse) that was focused onto the filled cuvette containing the desired solution. The experimental data thus collected are time courses at single wavelength; they are converted to absorbances by means of the IGORPRO package (Wavemetrics).…”
Section: Methodsmentioning
confidence: 99%